Grey’s brand Marketing Journey: An overview of SAVLON rebranding from Grey’s perspective. - Jahan, Marjana (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.